Matching Points with Disks with a Common Intersection - Perez-Lantero, P (Elsevier B.V., 2019)
We consider matchings with diametral disks between two sets of points R and B. More precisely, for each pair of matched points p∈R and q∈B, we consider the disk through p and q with the smallest diameter. We prove that for any R and B such that |R|=|B|, there exists a perfect matching such that the diametral disks of the matched point pairs have a common intersection. In fact, our result is stronger, and shows that a maximum weight perfect matching has this property. © 2019 Elsevier B.V.
Keywords: Diametral disks; Perfect matching; Bichromatic geometric matching; Helly s theorem